Acclimation of Panicum maximum to different light regimes. Effect of subsequent defoliation - Páez, Alejandra; González, Maria; Villasmil, Jose (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Plant performance depends directIy on the available light, and defoliation may change plant structure by altering light interception. These two factors, irradiance and defoliation, together may cause important effects on growth patterns. The present research was conducted to evaluate growth and biomass allocation of guineagrass (Panicum maximum Jacq.), a C4 shade-tolerant plant, after acclimation to three light regimes, and to establish the effect of defoliation. After seedling emergence, plant height and the number of leaves and culms were recorded daily for 60 d. Harvests were made at 33 d and 63 d after planting. Other plants were clipped at 20 or 40 cm or left undefoliated (controls). Guineagrass was taller in the shade, with fewer leaves and culms than in full sunlight. In partial shade, leaf area and dry biomass were reduced less than in deep shade. Leaf area ratio (LAR) increased with decreasing irradiance due mainly to increases in specific leaf area (SLA), although leaf weight ratio (LWR) contributed to this effect. The biomass response to clipping was fairly similar in an irradiances, but there was a significant interaction of height of clipping and irradiance on root/shoot ratio (R/S). Root/Shoot ratio decreased with clipping in deep shade and fullsunlight. The reduction was greatest under full sunlight conditions. The increases in LAR induced by shading may have adaptive significance in guineagrass. LWR was more affected by clipping than other biomass parameters, because it increased with more intense clipping, regardless of the irradience regime. Changes in irradiance affected LAR and SLA, whereas the effect of clipping was significantly greatest on LWH. Generally, biomass allocation of guineagrass was affected by clipping and irradiance, and growth depended on the irradience received.